141 Data sharing projects in end of life care – easier, harder, or just as fiercely complex as any other?. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Petrova, Mila; Barclay, Stephen
Abstract : Background: Electronic Palliative Care Coordination Systems (EPaCCS), enabling data sharing across care settings, have been under development in England for over nine years and are expected to cover all areas of the country by 2020. Data sharing (technically termed 'health information exchange'?, HIE) projects are, however, amongst the most difficult projects of health information technology (HIT) implementation. We report on a sub-study of 'Prepared to Share?', a mixed methods realist evaluation of The Cambridgeshire and Peterborough Project for Data Sharing in End of Life Care, nested in broader research on data sharing and EPaCCS. Methods: 44 participants were interviewed using principles of realist and episodic interviewing. Preliminary analysis of nine interviews and four existing reviews on HIE and HIT, covering 135 studies, contributed to an initial analysis framework. Framework and thematic analysis principles and 'pluralist' coding informed by the philosophy of science of J. Dupre were applied in the analysis. Results: We identified >460 challenges and >300 drivers to implementing EPaCCS and data sharing projects more broadly, the majority of them richly described in the interviews. The main sources of challenges were: the existence of 'alternatives', i.e. primarily well entrenched and thus easier ways of working, but also other data sharing solutions; generic resource constraints within the health system; information governance issues; generic IT infrastructure challenges; insufficient adaptability, capacities for personalisation and flexibility of the solution; and generic features of the health system, such as its fragmentation. 'Expected benefits' and 'training, education and awareness raising' were the only higher-level categories where drivers outweighed challenges. Conclusions: EPaCCS projects and research need to draw on and contribute more to existing HIE and HIT research. EPaCCS teams and users are learning the hard way many lessons which are already described in this broader research literature.